2000
DOI: 10.1029/1999je001130
|View full text |Cite
|
Sign up to set email alerts
|

Compositional studies of the Orientale, Humorum, Nectaris, and Crisium lunar basins

Abstract: Abstract. We have used full-resolution (250 m/pixel) Clementine images to map the compositions of ejecta from four multiring basins on the Moon: Orientale, Humorurn, Nectaris, and Crisium. All basins have relatively feldspathic ejecta, with iron contents ranging from 2 to 6 wt % Fee. Some basins show remarkably homogeneous ejecta blankets (Orientale), while others display distinct compositional zoning within exterior sectors of the basin (Crisium); in some cases this zoning correlates with morphologically obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 19 publications
8
49
0
Order By: Relevance
“…Here, we propose a new crust model and provide the rationale behind our model in comparison to previously proposed models. Korotev et al (2003) suggested a possible crustal configuration of a ferroan anorthositic upper layer and a magnesian, slightly more mafic lower layer by linking the FAN and the magnesian feldspathic rocks as the precursor of the magnesian granulites with the remotely sensed crustal configuration (Tompkins and Pieters, 1999;Bussey and Spudis, 2000;Hawke et al, 2003). This model seems to be consistent with the simultaneous occurrence of the magnesian and ferroan granulites within the Apollo samples and the feldspathic lunar meteorites.…”
Section: Asymmetric Crust Modelsupporting
confidence: 69%
See 1 more Smart Citation
“…Here, we propose a new crust model and provide the rationale behind our model in comparison to previously proposed models. Korotev et al (2003) suggested a possible crustal configuration of a ferroan anorthositic upper layer and a magnesian, slightly more mafic lower layer by linking the FAN and the magnesian feldspathic rocks as the precursor of the magnesian granulites with the remotely sensed crustal configuration (Tompkins and Pieters, 1999;Bussey and Spudis, 2000;Hawke et al, 2003). This model seems to be consistent with the simultaneous occurrence of the magnesian and ferroan granulites within the Apollo samples and the feldspathic lunar meteorites.…”
Section: Asymmetric Crust Modelsupporting
confidence: 69%
“…3). Combined with the crustal zonation indicated by remote sensing (Bussey and Spudis, 2000;Hawke et al, 2003), where a more mafic layer should be located beneath a highly feldspathic layer in the crust, it is the magnesian portion that comprises a magnesian anorthositic, upper crust and a magnesian troctolitic, lower crust, and the ferroan portion that is formed by a ferroan anorthositic, upper crust and a ferroan noritic, lower crust (Fig. 3).…”
Section: Asymmetric Crust Modelmentioning
confidence: 99%
“…On average, the crust is~40 km thick, as shown by recent models incorporating Gravity Recovery and Interior Laboratory (GRAIL) gravity and Lunar Orbiter Laser Altimeter (LOLA) topography data [Wieczorek et al, 2013]. Several lines of evidence from lunar sample analyses as well as remote sensing studies suggest that the mafic content of the crust increases with depth [Reid et al, 1977;Ryder and Wood, 1977;Bussey and Spudis, 2000;Tompkins and Pieters, 1999;Cahill et al, 2009;Ohtake et al, 2009]. However, impacts throughout lunar history have fractured, brecciated, mixed, melted, and redistributed crustal materials.…”
Section: The Evolution and Stratigraphy Of The Lunar Crust And Mantlementioning
confidence: 99%
“…(2) The noritic impact melt breccias sampled at the Apollo stations most likely have a deep crustal origin (e.g., [42]). (3) The ejecta blankets of large basins have been shown to be more ma¢c than average crustal materials (e.g., [43]). (4) The compositions of some central peaks in complex craters are highly noritic or troctolitic (e.g., [44]).…”
Section: The Density and Structure Of The Lunar Crustmentioning
confidence: 99%